Development and testing of a stifle function score in dogs - Gundersen, Katie; Millis, Darryl; Zhu, Xiaojuan (Frontiers in Veterinary Science, 2022)
The purpose of this study was to develop and test a quantitative stifle function score (SFS) in dogs with unilateral cranial cruciate ligament disease by combining clinical measures and functional tests. The objective of this study was to compare the proposed SFS to a symmetry index (SI) calculated from objective ground reaction forces (GRF). We hypothesized that the SFS would have a strong correlation with SI. Dogs with surgically and non-surgically treated unilateral cranial cruciate ligament rupture and dogs with no known musculoskeletal problems were included in the study. Each dog was scored using the SFS and trotted across a force platform to obtain GRFs and calculate the SI, based on vertical GRFs. Fourteen items were included in the SFS: limb use at a walk, limb use at a trot, lameness at a walk, lameness at a trot, stair climbing, sit-to-stand, dancing, pain response, stifle effusion, thigh circumference/muscle atrophy, stifle extension, stifle flexion, and cranial drawer/tibial thrust, with each item scored based on previously determined criteria. A perfect SFS would receive a score of 100. Twenty-seven dogs were included in the study: twenty-one with unilateral cranial cruciate ligament disease and six control dogs. The mean SFS was 71.56 out of 100. To further characterize the association between SFS and SI the degree of gait asymmetry using SI was classified as less than 5%, 5-10%, 10-20%, 20-25%, and greater than 25% difference between the pelvic limbs for all dogs. The mean SFS for each of the five categories were 97.8, 85.2, 65.4, 63, and 56.4 respectively. Correlation of symmetry index and SFS was -0.863 (p < 0.0001). All of the individual evaluated tests in the score were significantly correlated with symmetry index except for pain response and stifle flexion. The SFS is in strong agreement with the symmetry index, as confirmed by Bland-Altman analysis. The SFS had significant correlation and agreement with symmetry index calculated from ground reaction forces. This SFS may be a useful, simple, and inexpensive tool to use in a clinical environment to monitor progression during the rehabilitation and recovery process following unilateral cranial cruciate ligament rupture.